The Left sided Acute Appendicitis in a Patient with Situs Inversus Totalis: A Case Report - Lacoul, Robal; Shrestha , Pratikshya (Journal of Bharatpur Hospital, 2025)
Situs inversus totalis (SIT) is a rare inherent disease in which the thoracic and abdominal organs are transposed. Acute appendicitis is one of the most common causes of emergency room visit requiring surgical treatment and mostly present with right lower quadrant abdominal pain. Symptoms of appendicitis in situs inversus may appear in left lower quadrant making the diagnosis difficult, however it can be based on physical examination findings and imaging modalities including USG, CT scan, chest X-ray and diagnostic laparoscopy. After establishing the diagnosis of acute appendicitis in a patient with SIT, surgical options are either laparoscopic or conventional appendectomy.